Duodenocaval Fistula in a Patient with Inferior Vena Cava Leiomyosarcoma Treated by Surgical Resection and Caval Polytetrafluoroethylene Prosthesis. (21st June 2015) - Ippolito, Davide; Querques, Giulia; Drago, Silvia Girolama; Bonaffini, Pietro Andrea; Sironi, Sandro
Abstract : Inferior vena cava (IVC) leiomyosarcoma represents an extremely rare disease that commonly involves the segment between the inflow of the renal veins and the inflow of the hepatic veins (46% of cases). We report the case of a patient affected by an IVC leiomyosarcoma, treated with surgical resection, caval reconstruction with polytetrafluoroethylene (PTFE), and right nephrectomy, followed by external beam radiotherapy. Oncological follow-up was negative for 17 years after this combined treatment, since the patient developed a duodenocaval fistula (DCF).